ANALISIS KEBUTUHAN PENGEMBANGAN E-SAKU UNTUK MENINGKATKAN KETERAMPILAN BERBAHASA MAHASISWA MANAJEMEN BISNIS INTERNASIONAL POLITEKNIK NEGERI BALI - Legi Aspriyanti; Runi Fazalani; I Nyoman Mandia (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study is grounded in the limited availability of independent learning media for students of the Business Administration Department at Politeknik Negeri Bali in enhancing their communication skills. The occurrence of code-mixing in language use has been identified as a factor that may result in unprofessional communication practices. This study aims to determine the extent of the need for developing an electronic pocket book of Indonesian lexical equivalents for students of the Business Administration Department at Politeknik Negeri Bali. The research adopts a quantitative approach with a descriptive design. Data were collected through a questionnaire and obtained using purposive sampling techniques. Data analysis was conducted using descriptive quantitative methods. The findings indicate that the development of an electronic pocket book (e-pocket book) is highly necessary to address the limitations of existing learning media and to support the improvement of communication skills among Business Administration students at Politeknik Negeri Bali